Determination of the Departure Pattern of Hajj Pilgrims Using the C45 Algorithm at the Ministry of Religion of Lubuk Pakam - Eliyana Syahfitri; Hasanul Fahmi (Putaka Timur Publisher, 2021)
Determination of the Departure Pattern of Hajj Pilgrims is currently very much needed by the Hajj organizers, especially at the Lubuk Pakam Ministry of Religion Office because the departure schedule for the Hajj pilgrims is still not regular, causing accumulation of data for pilgrims who will be dispatched to the holy land, but with The number of pilgrims who will depart is made to determine the pattern of Hajj departures with the C4.5 Algorithm to make it easier for the staff of the Hajj organizers to determine at what age they should be sent to the holy land.